Challenging Inequality: Analyzing the Portrayal of Black Women Workers in 'Self Made' through Feminist Stylistic Lens - Annisa Sri Wulan; Agwin Degaf (Lire Journal)
The physical appearance, particularly beauty standards influenced by social constructs, significantly impacts a woman's self-esteem and employment opportunities. Regrettably, black women, particularly African-American women, often experience marginalization due to societal beauty standards, racial biases, and gender discrimination within patriarchal settings. In light of this, our research employs the miniseries "Self-Made" to delve into how the dialogue spoken by the characters in the miniseries reflects the experiences of black women in the workforce. We utilize a qualitative descriptive research method with a feminist stylistic discourse analysis approach, following Sara Mills' methodology. Employing both word, phrase, and sentence-level analysis along with discourse-level examination, our study reveals the negative and degrading portrayals of black women in terms of their physical appearance, profession, and their place as women of the Negro race. Nevertheless, we also unearth instances where black women workers are depicted positively, reflecting their courage and empowerment in confronting racial stereotypes and patriarchal power. Our research aims to enhance understanding of the issues faced by black women by examining how they are represented in relation to their intersectional identities. Moreover, it highlights the significance of tackling preconceptions and biases present in media depictions, pushing for a society that is more inclusive and fairer.